Contemporary expropriations: state support for supplementary healthcare in Brazil - Alves, Pâmela Karoline Lins; Santos, Viviane Medeiros dos (Argumentum, 2020)
This article analyses the process of contemporary expropriation regarding social rights, following the outline of Brazilian health policy. The objective is to highlight how this process is evidenced in supplementary healthcare. The results of these discussions are based on a historical-critical analysis of the expropriation process, carried out from bibliographic research and information obtained through documentary research on the databases of the National Agency for Supplementary Health, the Transparency Portal of the Internal Revenue Service and the Ministry of Health. The study concludes that the expropriation of rights is demonstrated in healthcare, either through disputes for public funds, through mechanisms of state support to supplementary health, such as tax waivers, or through the commodification of health, and places the open market pathway as being the best and most efficient alternative for care and access to health.